Clinical role of bisphosphonate therapy - Hampson G; Fogelman I (Dove Medical Press, 2012)
Geeta Hampson,1,2 Ignac Fogelman1,31Osteoporosis Screening Unit, Guy’s Hospital, 2Department of Chemical Pathology, St Thomas’ Hospital, 3Department of Nuclear Medicine, Guy’s Hospital, London, UKAbstract: Bisphosphonates (BPs) are synthetic analogues of pyrophosphate. They inhibit bone resorption and are therefore widely used in disorders where there are increases or disruptions in bone resorption. This includes postmenopausal osteoporosis, glucocorticoid-induced osteoporosis, Paget’s disease of bone, and malignancy-related bone loss. To best understand the clinical application of BPs, an understanding of their pharmacokinetics and pharmacodynamics is important. This review describes the structure, pharmacology and mode of action of BPs, focusing on their role in clinical practice. Controversies and side effects surrounding their use will also be discussed.Keywords: pyrophosphate, bone resorption, postmenopausal osteoporosis, glucocorticoid-induced osteoporosis, Paget’s disease of bone, malignancy-related bone loss